12- and 24-Month-Old Infants’ Search Behavior Under Informational Uncertainty - Kim, Sunae; Sodian, Beate; Proust, Joëlle (Frontiers in Psychology, 2020)
Infants register and react to informational uncertainty in the environment. They also form expectations about the probability of future events as well as update the expectation according to changes in the environment. A novel line of research has started to investigate infants’ and toddlers’ behavior under uncertainty. By combining these research areas, the present research investigated 12- and 24-month-old infants’ searching behaviors under varying degree of informational uncertainty. An object was hidden in one of three possible locations and probabilistic information about the hiding location was manipulated across trials. Infants’ time delay in search initiation for a hidden object linearly increased across the level of informational uncertainty. Infants’ successful searching also varied according to probabilistic information. The findings suggest that infants modulate their behaviors based on probabilistic information. We discuss the possibility that infants’ behavioral reaction to the environmental uncertainty constitutes the basis for the development of subjective uncertainty.